The use Bacillus cereus Phospholipase C in Prophylaxis and Treatment of Thromboplastin Induced Thrombosis in Mice - Al-Jaff, Bahrouz M. A.; Mohammed, Dlnya A. (Sulaimani Journal for Pure and Applied Sciences, 2005)
Volumes of crude cell free filtrate and steps of partial purified phospholipase C were prepared from non-toxigenic bacilhis cereus isolate. Also concentraions of highly purifed preparation (ICN) was used. Prophylaxis against greater than LD50 thrombopastin (0.0612mg/mouse) revealed recovery of mice with 97% 100% and 97% for cell free filtrate, haemolysin cured and sephadex cluted phospholipase C respectively with no significant differences among injection time intervals while the pure preparation recovered 97% mice with a significant differences among time intervals . Treatment by post thrombosis induction revealed that cell ree filtrate, partial purification steps and the highly purified phospholipase C recoverd 98% mice with no significant differneces among injection time intercals . The haematological parameters PCV, RBC count and platelet count remained within normal range after 12 hours of injection, These results suggested the possibility of using partially purified and highly purified phospholipase C as prophylactiv agent against infarction in man .
Keywords: B cereus; thrombosis; thromboplastin; prophylaxis